Fast trapped particle motion in Uragan-2M stellarator with embedded magnetic mirror - Moiseenko, V.E.; Nemov, V.V.; Kalyuzhnyi, V.N.; Ågren, O. (Вопросы атомной науки и техники, 2014)
The magnetic configuration of a stellarator with an embedded magnetic mirror is arranged in the Uragan-2M experimental device by switching off one toroidal coil. The motion of particles magnetically trapped in the embedded mirror is analyzed numerically with use of motional invariants. It is found that without electric field the particle quickly drift out of the mirror. Sufficiently small radial electric field can make the drift trajectories closed that substantially improve particle confinement. It is remarkable that the improvement acts both for positive and negative charges.